2022
DOI: 10.3390/app122412966
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Online Gamified Learning Intentions of College Students: A Technology-Learning Behavior Acceptance Model

Abstract: With the popularity of online education, multiple technology-based educational tools are gradually being introduced into online learning. The role of gamification in online education has been of interest to researchers. Based on learners’ visual, auditory, and kinesthetic (VAK) learning styles, this study uses an empirical research method to investigate the behavioral intention of students to participate in online gamified classrooms in selected universities located in Guangdong province and Macao. The main co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…Additionally, perceived enjoyment is also found to be one of the antecedents of continuance use intention among HEI learners on a gamified m-learning application, as it was found to have a positive influence, supporting hypothesis H3. This also agrees with the finding by Yan et al (2022), which proved that perceived enjoyment has a significant positive influence on the student's intention to participate in an online gamified classroom. Each participation will boost their desire for further usage.…”
Section: Verification Of Th E Structural Modelsupporting
confidence: 91%
“…Additionally, perceived enjoyment is also found to be one of the antecedents of continuance use intention among HEI learners on a gamified m-learning application, as it was found to have a positive influence, supporting hypothesis H3. This also agrees with the finding by Yan et al (2022), which proved that perceived enjoyment has a significant positive influence on the student's intention to participate in an online gamified classroom. Each participation will boost their desire for further usage.…”
Section: Verification Of Th E Structural Modelsupporting
confidence: 91%
“…Researchers have continuously upgraded and extended TAM based on TAMs such as TAM2, TAM3, UTAUT, UTAUT 2, etc. [26][27][28][29][30][31][32]. Moreover, the Robotic Architectural Technology Acceptance Model (RATAM), a new high-tech acceptance theory model for AI robot architecture design contexts, provides new insights into the future development of AI in architectural design [33].…”
Section: Introductionmentioning
confidence: 99%
“…TAM is now widely used in different aspects of new technologies and confirmed that perceived usefulness (PU) and perceived ease of use (PEOU) have a significant impact on user acceptance. Researchers have continuously upgraded and extended TAM based on TAM, such as TAM2, TAM3, UTAUT, UTAUT 2, etc [26][27][28][29][30][31][32]. Although RATAM, a new high-tech acceptance theory model for AI robot architecture design contexts, provides new insights into the future development of AI in architectural design [33].To our knowledge.…”
Section: Of 22mentioning
confidence: 99%
“…These models provide system developers with a better way to control user BI [46]. For example, the Technology Acceptance Model for the Elderly (STAM) explores the acceptance of new technologies among older Hong Kong Chinese [47]; the Technology-Organization-Environment (TOE) framework combined with TAM examines the factors influencing end-user ATT and BI of AI-based technologies in construction companies [28]; the Learning Behavior Acceptance Model (T-LBAM) explores students' participation in gamified online courses intrinsic influences on willingness [26]. It is important to notice that there are many influencing factors in TAM, and these factors vary significantly across different research areas.…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%